Annually recurring erythema annulare centrifugum: a case report. (December 2015) - Mandel, Victor; Ferrari, Barbara; Manfredini, Marco; Giusti, Francesca; Pellacani, Giovanni
Abstract Introduction Erythema annulare centrifugum is a rare cutaneous disease characterized by erythematous and violaceous annular plaques that usually involved the thighs and the legs. The eruption may be associated with an underlying disease and its accompanying characteristic symptoms. For these reasons, a full physical examination should be conducted to exclude underlying disorders. Annually recurring erythema annulare centrifugum is a rare and peculiar variant of erythema annulare centrifugum with the same clinical and histopathological characteristics. The lesions of annually recurring erythema annulare centrifugum tend to regress spontaneously after a variable period of days to months with yearly recurrence for many years. Case presentation We present the case of a 46-year-old caucasian woman affected by annually recurring erythema annulare centrifugum, which is a peculiar form of superficial erythema annulare centrifugum. The lesions have the same clinical and histopathological characteristics of the classical superficial form of erythema annulare centrifugum and tend to regress spontaneously after a variable period of days to months. In our case, no precipitating factors were identified and no underlying diseases were found. Every year for the last 12 years the lesions started to appear in the summer months and regressed spontaneously in autumn. Conclusions Cases of annually recurring erythema annulare centrifugum are rarely reported in the literature and generally no causative agent can be detected. The main feature of annually recurring erythema annulare centrifugum is the constant annual and seasonal recurrence of the lesions for many years.